Influence of Socioeconomic and Working Status of the Parents on the Incidence of their Children’s Dental Caries - Niha Naveed1 , Kishorekumar S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dental caries, or tooth decay, is an infectious process involving breakdown of the tooth enamel.Children aresusceptible to caries as soon as the first teeth appear, which usually occurs around age 6 months.It is knownthat socioeconomic status affects the health-related quality of life of children.Family income, occupationalstatus, and educational achievement are socio-economic status indicators that have been found to affect thelife opportunities of an individual.